Assessment of effectiveness of maize seed treated with cyantraniliprole and thiamethoxam for management of fall armyworm, Spodoptera frugiperda (J. E. Smith) - Chinwada, P.; Fiaboe, K.; Akem, C.; Dixon, A.; Chikoye, D. (Elsevier, 2023)
The effectiveness of maize seed treatments for management of fall armyworm (FAW) (Spodoptera frugiperda) was evaluated under natural infestation conditions in Zambia in 2019, 2020 and 2022. Two seed treatments were tested: cyantraniliprole (Fortenza® 600 FS) + thiamethoxam (Cruiser® 600 FS) (combination marketed as Fortenza® Duo) and Fortenza® 600 FS. Other treatments included each of the two seed treatments supplemented with threshold-based rotational sprays of Denim Fit® 50 WG (emamectin benzoate + lufenuron) and Ampligo® (chlorantraniliprole + lambda cyhalothrin), Denim Fit/Ampligo alone, untreated controls, Ecoterex® 0.5% GR (deltamethrin + pirimiphos methyl) and Mythic® FN SC (chlorantraniliprole). The incidence of FAW-infested plants and plant damage scores were recorded weekly for 4–5 weeks post-emergence. At harvest, grain yield, yield increase over untreated control and cost-benefit ratios were also determined. Although there were some seasonal variations in treatment effectiveness, plots established from Fortenza Duo-treated seed generally had significantly lower plant damage within the first 3–5 weeks of growth. The number of follow-on insecticide sprays were reduced from 2 to 1 in February 2022 plantings in plots established from Fortenza Duo-treated seed. Grain yields were highest in the Denim Fit/Ampligo plots (December 2021 plantings) and Fortenza Duo + Denim Fit/Ampligo plots (December 2021 and February 2022 plantings). In both plantings of the 2021-22 season, mean yield increase over untreated control was highest in Fortenza Duo + Denim Fit/Ampligo plots. Cost-benefit ratios were, however, highest where Fortenza Duo-treated seed was planted without any follow-on chemical sprays and lowest and negative in sole Fortenza plots. Due to method of application and systemic action, Fortenza Duo maize seed treatments may be a perfect fit in FAW integrated pest management (IPM) programs where there is need for judicious pesticide use.